Christian music in scripture and tradition - Damian, Lucian (Technium Social Sciences Journal, 2022)
Religious music has always been man’s attempt to express the relationship between the Divine and the human. Through it, human nature takes part in the love of the Holy Trinity, participating in power, in prayer and in spirit, in the immanence of God. Divine revelation is easily revealed to man through theology expressed in religious music, and man, regardless of his theological knowledge, begins to feel and live in the love of God.